A família da criança-problema na escola : estudo de fenomenologia sociológica aplicada à enfermagem - Monteiro, Ana Ruth Macedo (2001)
Working with families is a chalenge for nursing, mainly when we speak of mental health promotion. The socialization of the individual begins inside his family at the school is probably the nearest opportunity in which take place the change of the experiences with another people. The child can, in his school context, reproduce a family conflict situation and be characterized is a problem child for not adapted to the school norms. Perceiving as indispensable the familiar context to promove to mental health. I intended with this study answer the following question: what’s the problem-child familiar lived type at the school? Beginning from the experiences lived by the subjects, I search for the comprehension of the problem- child familiar lived type at the school, describing the structure of each family, their interrelations and the situations lived as manifestation of their familiar type, having by support the Sociological Fenomenology. At first, it was interviewed ten teachers from first and fourth series, from a municipal public school, to identify the children who where considered problem at school. After this, it began the visits to those children’s families with observations at their houses, followed by interviews. It was interviewed seventeen families, with two meetings by families at least. The answers composed the following concrete categories: in motivation because their lived type — the necessary maintenance for the survival, Action with children, the family relations and feelings about the life; and the in-order-to motive in the lived type — what the expect from the children and family and personal projects. Whit the intersection between the categories, I search for the meaning of the subjective action. Looking for this meaning in this families, I perceived how the confront social and economic multiple problems and that inside these conflicts, they try to offer for the their members support to confront challenges and also find out altematives to support this reality with wishes and aspirations. In the intersubjective world, the families utilizes its experiences already worked to defined its biografycal situation, making a relation between the Ourselves and its contemporaneous, in a social-historic world. However its wasn’t possible to comprise the meaning of the families subjective actions in all its totality, but partially, because the comprehension is a always opened horizon. I perceived, in the families subjective actions in the customary world, a reflexe of the social reality present in our real world, in which there are the cultural, economic and politic questions, that interfere in health, especially in the mental health. And when I remit to an actual conjunture reading, I perceive that the studied families are inserted in a city context that grows without a politic and social structure in the same proportion. Working with families is a big challenge for nursing, since it involves the care to individual in the several stages from his vital cycle. And, as a group, with several age degrees, its development cycle is situated in costumary world in a such peculiar way. Considering all these aspects, the nursing will be on the way to get an action in mental health promotion for families.